Linguistic ideologies and hierarchical assessment of standard Spanish in Peruvian university speakers - Vera Buitrón de Gratal, Mervi Paola (2021)
Peru's diverse scenario constitutes a context of linguistic interaction in which, from an eminently scientific perspective, each of the Peruvian languages, as well as the diverse manifestations of Spanish itself, is invaluable. Despite the many efforts to make visible and recognize the value of linguistic heterogeneity, Spanish stands as the most prestigious language for Peruvians. The present study aims to determine the way in which linguistic ideologies define the occurrence of attitudes and valuations of standard Spanish to the detriment of other varieties that are subject to negative weightings. The corpus was obtained through semi-directed interviews and surveys applied to university students; and, according to critical discourse analysis (CDA), it is detected that linguistic ideologies permeate and guide the students' valuational framework, so that a hierarchization of standard Spanish is established above any of the dialects not only in the university environment but also outside it; Consequently, sociolinguistic practices themselves imply the manifestation of biases regarding vertical relations between Spanish and minority languages in broad terms, and between standard Spanish and Peruvian regional dialects.